A Pyrazine‐Based Polymer for Fast‐Charge Batteries - Mao, Minglei; Luo, Chao; Pollard, Travis P.; Hou, Singyuk; Gao, Tao; Fan, Xiulin; Cui, Chunyu; Yue, Jinming; Tong, Yuxin; Yang, Gaojing; Deng, Tao; Zhang, Ming; et al. (Angewandte Chemie (International ed.), 2019)
The lack of high‐power and stable cathodes prohibits the development of rechargeable metal (Na, Mg, Al) batteries. Herein, poly(hexaazatrinaphthalene) (PHATN), an environmentally benign, abundant and sustainable polymer, is employed as a universal cathode material for these batteries. In Na‐ion batteries (NIBs), PHATN delivers a reversible capacity of 220 mAh g−1 at 50 mA g−1, corresponding to the energy density of 440 Wh kg−1, and still retains 100 mAh g−1 at 10 Ag−1 after 50 000 cycles, which is among the best performances in NIBs. Such an exceptional performance is also observed in more challenging Mg and Al batteries. PHATN retains reversible capacities of 110 mAh g−1 after 200 cycles in Mg batteries and 92 mAh g−1 after 100 cycles in Al batteries. DFT calculations, X‐ray photoelectron spectroscopy, Raman, and FTIR show that the electron‐deficient pyrazine sites in PHATN are the redox centers to reversibly react with metal ions. Poly(hexaazatrinaphthalene) (PHATN), an environmentally benign, abundant and sustainable polymer, is employed as a universal cathode material for metal batteries. Exceptional performance is observed in Na and in more challenging Mg and Al batteries. The electron‐deficient pyrazine sites in PHATN are the redox centers to reversibly react with metal ions.